+0  
 
0
36
1
avatar

Suppose x + y = a and x^3 + y^3 = b where a is not equal to 0.  Find xy in terms of a and b.

 May 8, 2020
 #1
avatar+21000 
0

x3 + y3  =  (x + y)(x2 - xy + y2)

 

Since  x3 + y3  =  b     --->     (x + y)(x2 - xy + y2)  =  b

Since  x + y  =  a         --->           a·(x2 - xy + y2)  =  b     --->     x2 - xy + y2  =  b/a     (equation #1)

 

Since  x + y  =  a     --->     (x + y)2  =  a2    

and  (x + y)2  =  x2 + 2xy + y2      --->     x2 + 2xy + y2​  =  a2     (equation #2)

 

Combining equation #2 and equation #1:     x2 + 2xy + y2​  =  a2 

                                                                      x -   xy + y2  =  b/a 

Subtracting:                                                           3xy         =   a2 - b/a

Rewriting:                                                               3xy        =  (a3 - b)/a

Dividing:                                                                   xy         =  (a3 - b) / (3a)

 May 8, 2020

16 Online Users

avatar